Effects of Mussel Peptides on Growth and Development and Microbial Community Structure of the Thick-Shelled Mussel Mytilus coruscus Plantigrades - Qian LIN; Zheng LI; Jinlong YANG; Fan MA; Xiao LIANG (Progress in Fishery Sciences)
The thick-shelled mussel Mytilus coruscus belongs to Mollusca, Lanellibranchia, Anisomyaria, Mytilidae, and Mytilus. Due to its flavor and nutritional and high economic values, M. coruscus is a common commercial shellfish in the coastal area of Zhejiang and Fujian in China, and is an important cultured mussel species in China. With the increasing development of coastal areas and the changing habitat conditions, aquaculture industry of M. coruscus is facing problems such as slow growth of juvenile mussels, low meat production rate, and individual miniaturization of adult mussels, which affects the sustainable development of the mussel industry and economic income. Conversely, prebiotics are commonly used exogenous additives in aquaculture. Prebiotics help the organism to absorb nutrients by changing the morphology of the gastrointestinal tract and regulating the composition of the microbial community. They can promote the growth and development of aquatic organisms, enhance resistance to pathogenic bacteria, and improve the absorption and utilization rate of feed to increase the output of aquatic products. As a protein hydrolysate, mussel peptide is also a probiotic element with high nutritional value and multiple functions such as antimicrobial, antioxidant, and immune enhancement. In particular, low molecular weight mussel peptide has the function of anti-lipid peroxidation protective activity and scavenging of excess free radicals, which can be used as a natural antimicrobial food additive. In aquaculture, mussel peptides are considered to be natural active ingredients for treating infectious diseases in marine species. Till date, the relationship between mussel peptides and the growth and development of the thick-shelled mussel M. coruscus remains unclear. Therefore, the optimal concentration of mussel peptide for the potential application of mussel peptides in the M. coruscus aquaculture industry must be determined. In this study, we focused on the effects of mussel peptides on the growth and development of the thick-shelled mussel M. coruscus and on the structural composition of microbial communities. The aim was to provide a theoretical basis for green and efficient aquaculture of the thick-shelled mussel M. coruscus. Here, the thick-shell mussel plantigrades used in the experiment were provided by Donghai Mussel Technology Innovation Service Co., LTD., Shengsi County, Zhejiang Province, China. It was used in the experiment after 1 week of temporary cultivation at 18 ℃ and a salinity of 30. Before the bioassays, these mussel plantigrades were cultured in the lab at 18 ℃ and 30 for 7 d. Five feeding treatment groups and one non-feeding control group were set up in the experiment. The treatment groups were fed mussel peptides at concentrations of 7, 9, 10, 70 and 90 mg/L, and each group was set up with three replicates. On days 7, 14, 21, 28, 42, and 56; 50 plantigrades were randomly selected from different treatment groups for growth measurement including shell length, shell height, and wet body weight. In addition, samples of plantigrades from different treatment groups were collected on days 28 and 56 to analyze the change in microbial communities before and after feeding. The results showed that, compared with the control group, feeding 9 mg/L of mussel peptides could significantly promote plantigrade growth and the shell length, shell height, and wet body weight were increased by 27.37%, 32.35%, and 115.49%, respectively. However, the mussel peptide concentration was too high (70 mg/L and 90 mg/L), which could cause lethal effects on the thick-shelled mussel M. coruscus plantigrades. The microbiome of the thick-shelled mussel plantigrades in the 28-day and 56-day treatment and control groups was analyzed by 16S rRNA gene amplification and sequencing. The results of the study showed that feeding 9 mg/L mussel peptides could alter the structural composition of the thick-shelled mussel plantigrade microbial community, such as increase in the abundance of Bacteroidota and Proteobacteria, and decrease in the abundance of Actinobacteriota. Simultaneously, an increase was observed in the diversity of beneficial bacteria such as Ruegeria, Tenacibaculum, Maribacter, Arenibacter, Octadecabacter, and Shewanella and reduction in the potentially pathogenic bacteria such as Rhodococcus and Aeromonas. Therefore, the appropriate amount of mussel peptides is useful for promoting the growth and development of the thick-shelled mussel M. coruscus plantigrades and optimizing their microbial community structure. In summary, mussel peptides have potential prebiotic functions and have the advantage of easy absorption of small molecules. By changing and adjusting the structure composition of the microbial community, mussel peptides increase the relative abundance of probiotics and reduce the relative abundance of potential pathogenic bacteria in the mussel microbial community of thick-shell mussel plantigrades, and promotes the growth and development of thick-shell mussel plantigrades. The current findings provide a basis and data support for the subsequent cultivation of marine bioactive peptides such as mussel peptides for enhancing shellfish juvenile aquaculture and the sustainable development of marine shellfish aquaculture.